Dilema Keamanan Mesir di Selat Bab el-Mandeb dalam Menghadapi Eskalasi Serangan Houthi terhadap Jalur Perdagangan Maritim Global (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study examines Egypt's security dilemma in the Bab el-Mandeb Strait in response to the escalation of Houthi attacks on global maritime trade routes. Since late 2023, Houthi attacks on commercial ships in the Red Sea have disrupted major sea trade lanes, posing a direct strategic threat to Egypt, which relies heavily on Suez Canal revenues as a primary source of national income. This research employs a qualitative approach with a descriptive-analytical method, using secondary data from academic journals, international policy reports, and credible news sources. The analysis is grounded in Security Dilemma theory and the concept of Maritime Security within the framework of International Relations. Findings show that Egypt faces a complex strategic dilemma: on one hand, it must safeguard its economic interests through stable Suez Canal operations; on the other, direct military intervention against the Houthis risks political backlash from Arab public opinion and entanglement in Yemen's civil war. Egypt's response has therefore been calibrated, prioritizing diplomatic channels and multilateral coalition participation over unilateral military action. This research contributes a novelty by specifically mapping Egypt's strategic constraints in the Red Sea as a middle power caught between great power competition and regional non-state actor threats.